Friksi dalam Interaksi Pribadi Ali Mochtar Ngabalin dalam Dialog Acara Mata Najwa di Trans 7: Kajian Kesantunan Perspektif Teori Robin Lakoff - Ilham, Ilham; Sukri, Sukri; Mahyudi, Johan (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to analyze the friction in Ali Mochtar Ngabalin's personal interactions in the Mata Najwa event dialogue on Trans 7 entitled gara-gara hashtags. This study uses a descriptive qualitative method with a polite approach to Robin Lakoff's theory. By analyzing 7 episodes of Mata Najwa, this study finds that Ali Mochtar Ngabalin's speech in the Mata Najwa dialogue can be said to be impolite even though the speech conveyed is formal and not assertive. This is because the choice of words, attitudes, and tone of voice during the dialogue does not meet the aspects in Robin Lakoff's theory. However, this research is not without its shortcomings, so it is hoped that further research will expand the object of study that does not only cover speech but also in terms of tone of voice, body gestures, and other